2012
DOI: 10.1159/000336205
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab for Chronic Urticaria: A Case Series and Overview of the Literature

Abstract: Omalizumab is a recombinant humanized monoclonal antibody that blocks the high-affinity Fc receptor of IgE. Omalizumab has been approved for the treatment of moderate to severe asthma; however, there is currently more and more data showing promising results in the management also of chronic urticaria. We present a case series of 19 patients with chronic urticaria treated in a university department with omalizumab and give an overview of the existing literature comprising an additional 59 cases as well as a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 29 publications
1
22
0
3
Order By: Relevance
“…Many case reports have already shown the beneficial effect of omalizumab in patients with recalcitrant physical urticaria [4, 21, 22, 25]. In addition to previously published reports, our case suggests that omalizumab may be an effective, rapid and safe treatment option in patients with cold contact urticaria who do not sufficiently respond to standard therapy as recommended by existing guidelines.…”
Section: Discussionsupporting
confidence: 69%
“…Many case reports have already shown the beneficial effect of omalizumab in patients with recalcitrant physical urticaria [4, 21, 22, 25]. In addition to previously published reports, our case suggests that omalizumab may be an effective, rapid and safe treatment option in patients with cold contact urticaria who do not sufficiently respond to standard therapy as recommended by existing guidelines.…”
Section: Discussionsupporting
confidence: 69%
“…: In randomized trials, side-effects reported in more that 3% of patients receiving consisted in headache, diarrhoea, joint pain, dysmenorrhoea and upper respiratory tract infections, without differences between the groups receiving active treatment and placebo [103]. …”
Section: Resultsmentioning
confidence: 99%
“…Our review is intended to provide a comprehensive, critical, and rigorous synthesis of this body of evidence and to provide an informed opinion on the use of omalizumab across the diverse patient phenotypes affected by CIU/CSU. As a systematic review, it extends and updates the clinical and product reviews and summaries on omalizumab in CIU/CSU published to date [27][28][29][30][31][32][33][34][35][36], and provides guidance to clinicians.…”
Section: Introductionmentioning
confidence: 90%